Structural and spectral studies of Ce3+ doped Sr3Y(BO3)3 nano phosphors prepared by combustion synthesis. (7th June 2022) - Hargunani, Sanjay Prakash; Sonekar, Rajkumar Pandurang; Singh, Anoop; Khosla, Ajit; Arya, Sandeep
ABSTRACT: In this work, a series of Ce 3+  activated Sr3 Y(BO3 )3  phosphors were synthesized by the solution combustion method. The synthesized phosphors were characterized via X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier-transform infrared (FTIR) spectroscopy for their structural and morphological studies. Further, the optical properties of phosphors were studied via photoluminescence emission (PLE) spectroscopy. The results showed a broad photoluminescence excitation wavelength band from 250 to 380 nm. The PLE spectrum consists of a major peak centered at 340 nm. Concentration quenching for 433 nm emission line is observed at 8 mol% of Ce 3+  ion and it is due to electrical multipolar interaction. The non-radiative transition between Ce 3+  ions occurs via dipole–dipole interaction for the concentration quenching of Ce 3+  in Ce 3+  doped Sr3 Y(BO3 )3 . The CIE-coordinates for PL emission at 8 mol% concentration of Ce 3+  are obtained as (X = 0.1677, Y = 0.0078).